Evocation of Trade Disputes Through Arbitration of The World Trade Organization - Herryani, Mas Rara Tri Retno; Rahma, Iklima Nur; Albar, Mohammad Haris Yusuf (Journal of Law, Politic and Humanities, 2025)
Arbitration is an independent, final and binding mechanism for resolving international commercial disputes within the framework of the WTO. There are two major international agreements on arbitration, namely the New York Convention and the ICSD Convention/Washington, which contains provisions in the form of "the law of arbitration”. Arbitration concerns several things, including party autonomy, competence, legal obligations, good ethics, efficiency, audit and modification, privacy and confidentiality, separation, limitation of judicial involvement, venue, and fair and impartial treatment. The advantages of arbitration include fast resolution, confidentiality, and freedom to choose arbitrators. However, there are also disadvantages that must be considered. For example, if the parties do not fulfill the requirements of the good faith rule, then the arbitral award will lose full legal force and effect. Therefore, the selection of arbitration as a method of dispute resolution must be done carefully by considering all relevant aspects and principles.